Loboplusia coreana sp. nov. from South Korea, only the second species of a genus originally described from Costa Rica (Diptera: Cecidomyiidae, Winnertziinae) - Jaschhof, Mathias; Ham, Daseul; Bae, Yeon Jae (Zootaxa, 2018)
The genus Loboplusia was recently introduced for a remarkable species of Diallactiini from the cloud forest of Costa Rica (Jaschhof 2016). Males of that species, Loboplusia zurqui Jaschhof, 2016, were found to differ fundamentally from other Diallactiini, with the following traits defining the genus. The scutum is provided with a bright membranous patch called the prescutellar window; setae on the legs, especially the tarsi, are fringed; the gonostylus consists of two lobes (not a single lobe as is the basic pattern in Diallactiini); and the bridge connecting the gonocoxites ventrobasally is markedly shortened (Jaschhof 2016: fig. 15). A diallactiine collected recently by one of us (YJB) in South Korea shows exactly the same characters and is no doubt congeneric with L. zurqui. At the same time there are clear distinctions in the genitalia indicating that the South Korean species is discrete, so it is described and named here L. coreana Jaschhof & Ham sp. nov. With a single species each in Central America and Eastern Asia, the genus Loboplusia has a distinctly odd distribution, a circumstance that is briefly discussed.